Changes in the Transcriptome and Chromatin Landscape in BRAFi-Resistant Melanoma Cells - Kiran Kumar Reddi; Praveen Guruvaiah; Yvonne J. K. Edwards; Romi Gupta; Romi Gupta (Frontiers in Oncology, 2022)
Metastatic and drug-resistant melanoma are leading causes of skin cancer–associated death. Mitogen-associated protein kinase (MAPK) pathway inhibitors and immunotherapies have provided substantial benefits to patients with melanoma. However, long-term therapeutic efficacy has been limited due to emergence of treatment resistance. Despite the identification of several molecular mechanisms underlying the development of resistant phenotypes, significant progress has still not been made toward the effective treatment of drug-resistant melanoma. Therefore, the identification of new targets and mechanisms driving drug resistance in melanoma represents an unmet medical need. In this study, we performed unbiased RNA-sequencing (RNA-seq) and assay for transposase-accessible chromatin with sequencing (ATAC-seq) to identify new targets and mechanisms that drive resistance to MAPK pathway inhibitors targeting BRAF and MAPK kinase (MEK) in BRAF-mutant melanoma cells. An integrative analysis of ATAC-seq combined with RNA-seq showed that global changes in chromatin accessibility affected the mRNA expression levels of several known and novel genes, which consequently modulated multiple oncogenic signaling pathways to promote resistance to MAPK pathway inhibitors in melanoma cells. Many of these genes were also associated with prognosis predictions in melanoma patients. This study resulted in the identification of new genes and signaling pathways that might be targeted to treat MEK or BRAF inhibitors resistant melanoma patients. The present study applied new and advanced approaches to identify unique changes in chromatin accessibility regions that modulate gene expression associated with pathways to promote the development of resistance to MAPK pathway inhibitors.